An exploration of west point cultural identity and ethnocentrism through the lens of systems theory - Vick, Michael D. (Kansas State University, 2021)
A significant gap exists in the body of literature concerning university military leadership programs concerning cultural identity and ethnocentrism. U.S. military leaders serve in all levels of government and corporate alike, and these leaders conduct warfare, most of which is non-lethal stability operations abroad. Military veterans serve in leadership positions in both corporate and government, many times interacting with people in other cultures. Military adult leadership programs to include the U.S. Military academies and ROTC programs shape the identity of these future leaders. The researcher explored how five future cadets discussed their cultural identity in relationship to other cultural identities. The researcher synthesized the cadet interviews with a sample of ten cadet essays, and thirteen physical artifacts (archetypes). The researcher explored the phenomenon shaped around ethnocentrism with the theoretical framework rooted in the assumptions of the primary scholars of grounded theory and further viewed the phenomena through the lens of systems theory. The researcher found that the West Point education system results in cadet identity that begins to homogenize by the end of the first year to a military cultural identity that is perpetually optimistic and somewhat nationalistic. Most of the cadets become much more accepting of each other’s sub-American cultural differences; however, the lack of exposure to global cultures results in a somewhat non-global cultural identity.
Keywords: Cultural identity; Military cultural identity; Ethnocentrism; Leadership; Racism; West Point